Determination of non-recrystallization temperature for niobium microalloyed steel - Akhtar, Mohammad Nishat; Khan Mohammed, Muneer; Khan, Sher Afghan; Afzal, Asif; Subbiah, Ram; Sheikh, Nazeer Ahmed; Husain, Murtuja; Butt, Mohammad Mursaleen; Othman, Abdul Rahim; Elmi, Abu Bakar (MDPI, 2021)
In the present investigation, the non-recrystallization temperature (TNR) of niobium-micro alloyed steel is determined to plan rolling schedules for obtaining the desired properties of steel. The value of TNR is based on both alloying elements and deformation parameters. In the literature, TNR equations have been developed and utilized. However, each equation has certain limitations which constrain its applicability. This study was completed using laboratory-grade low-carbon Nbmicroalloyed steels designed to meet the API X-70 specification. Nbmicroalloyed steel is processed by the melting and casting process, and the composition is found by optical emission spectroscopy (OES). Multiple-hit deformation tests were carried out on a Gleeble® 3500 system in the standard pocket-jaw configuration to determine TNR. Cuboidal specimens (10 (L) * 20 (W) *20 (T) mm3) were taken for compression test (multiple-hit deformation tests) in gleeble. Microstructure evolutions were carried out by using OM (optical microscopy) and SEM (scanning electron microscopy). The value of TNR determined for 0.1 wt.% niobium bearing micro-alloyed steel is ~ 951 C. Nb- micro-alloyed steel rolled at TNR produce partially recrystallized grain with ferrite nucleation. Hence, to verify the TNR value, a rolling process is applied with the finishing rolling temperature near TNR (~951 C). The microstructure is also revealed in the pancake shape, which confirms TNR.